2019
DOI: 10.1136/vr.104923
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium aviumsubspeciesparatuberculosisseroconversion in dairy cattle and its association with raised somatic cell count

Abstract: This retrospective case–control study investigates the relationship between seroconversion to Mycobacterium avium subspecies paratuberculosis (MAP) and raised somatic cell count (SCC). The study consists of 112 case cows from three dairy farms in the UK; for each case cow with a positive antibody titre, there was a seronegative control cow for comparison. Seroconversion was monitored using milk ELISA antibody titres for MAP taken at quarterly intervals. SCCs were recorded at the time a positive antibody titre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 39 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Significantly higher SCC in MAP positive animals or herds than in negative animals or herds were reported in several studies ( 33 , 42 , 62 , 66–68 ). Ozsvari et al ( 42 ), for example, found that milk ELISA positive cows had on average a higher SCC by 41.4 × 1,000 cells/ml, which is equivalent to an increase of 35.8%.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…Significantly higher SCC in MAP positive animals or herds than in negative animals or herds were reported in several studies ( 33 , 42 , 62 , 66–68 ). Ozsvari et al ( 42 ), for example, found that milk ELISA positive cows had on average a higher SCC by 41.4 × 1,000 cells/ml, which is equivalent to an increase of 35.8%.…”
Section: Resultsmentioning
confidence: 57%
“…A significant decrease in milk yield for positive animals was observed in most studies, but a significant increase in milk yield, was also reported in few publications, depending on the stage of infection ( 30 , 31 , 50 , 61 ). In six publications, no significant difference was observed ( 33 , 46 , 47 , 62–64 ) and in five publications it was not stated whether the observed difference was significant ( 34 , 44 , 49 , 65 , 66 ).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation